2016
DOI: 10.5539/ass.v12n10p180
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Personal Values and Perceived Social Support in Developing Socially Responsible Consumer Behavior

Abstract: Corporate social responsibility (CSR) is a longstanding theme in marketing research. Although plenty of research have been done to examine the influence of CSR activities on consumer behavior, less attention is paid to explore the psychological factors that shape consumer's socially responsible behavior (SRB). The current research addresses this gap by reviewing and comparing the literature from psychology and marketing streams that moves towards a degree of convergence. It examines the psychological role of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
2
0
1
Order By: Relevance
“…El consumidor asocia sus actitudes de compra con sus creencias y valores, por lo que es uno de los aspectos que mas contribuye a la capacidad de generación de conciencia medioambiental con relación al bienestar económico, el apoyo emocional, el modo de vida y los procesos sociales (Song y Kim, 2018). De tal forma que los grupos sociales son un punto de comparación de los valores adquiridos en su núcleo familiar, los cuales permiten modificar su perspectiva en función de la socialización de los miembros, las normas de comportamiento que son impuestas en cada sociedad y la formación de conceptos propios generados a partir de experiencias (Ali y Mandurah, 2016). Siendo así, involucra en su vida las actividades que entiende que aporta al medioambiente tanto por lo que consume y evita consumir (Robinson y Schänzel, 2019).…”
Section: Actividades De Consumo Responsableunclassified
“…El consumidor asocia sus actitudes de compra con sus creencias y valores, por lo que es uno de los aspectos que mas contribuye a la capacidad de generación de conciencia medioambiental con relación al bienestar económico, el apoyo emocional, el modo de vida y los procesos sociales (Song y Kim, 2018). De tal forma que los grupos sociales son un punto de comparación de los valores adquiridos en su núcleo familiar, los cuales permiten modificar su perspectiva en función de la socialización de los miembros, las normas de comportamiento que son impuestas en cada sociedad y la formación de conceptos propios generados a partir de experiencias (Ali y Mandurah, 2016). Siendo así, involucra en su vida las actividades que entiende que aporta al medioambiente tanto por lo que consume y evita consumir (Robinson y Schänzel, 2019).…”
Section: Actividades De Consumo Responsableunclassified
“…Therefore, we investigate whether supporting others by participating in this type of celebration can lead to positive outcomes for the participant in the form of increases in perceived social support on the part of the participant. Second, because perceived social support has been associated with many positive outcomes, including playing an important role in the development of socially responsible behavior among consumers (Ali and Mandurah 2016), we explore whether there are additional downstream consequences of celebrations for others who are not directly involved in the celebration. Specifically, we examine whether increased perceived social support as a result of participating in this type of celebration will lead to a greater willingness to give back to others, thereby demonstrating broader policy implications of this work.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Van der Werff et al 24 determined that the relationship between biospheric value and environmental preference, intention, and behavior was completely mediated by environmental self-identity. Though there is no literature on the relationship between environmental personal social responsibility and biosphere values, Ali and Mandurah 25 observed that higher self-transcendence values led to higher levels of social responsibility among consumers. Therefore, we could hypothesize that:…”
Section: Extended Theory Of Value-identity-personal (Vip) Norm Model ...mentioning
confidence: 99%